Pendekatan Sosiologis dalam Memahami Praktik Keberagamaan Umat Islam - Dahlia Farina; Julhadi Julhadi; Sri Wahyuni (Lembaga Yasin AlSys, 2026)
Studies of Muslim religious practice have largely relied on theological and normative perspectives, while analyses based on sociological approaches that treat religious practice as a social phenomenon remain relatively limited. This study aims to analyze the forms of religious practice among Muslims, identify the social factors that influence these practices, and explain the relevance of a sociological approach for understanding the dynamics of religiosity in society. A qualitative approach with a case study design was employed, involving 15 participants selected through purposive sampling, consisting of religious leaders and members of the Muslim community. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using thematic analysis through the stages of data reduction, coding, categorization, and conclusion drawing. The findings show that Muslim religious practice manifests in two main dimensions: ritual practice (congregational prayer, recitation of the Qur’an, and study circles) and social practice (charitable giving, gotong royong, and community-based religious activities). Family, social environment, religious education, and the role of religious leaders were found to be key determinants shaping patterns of religious practice, while variations in the intensity of practice were influenced by personal conditions such as level of busyness and access to religious activities. These results affirm that religious practice is the outcome of dynamic interaction between individuals and surrounding social structures, and thus a sociological approach is relevant and necessary for understanding the forms of Muslim religiosity more comprehensively. Theoretically, this study enriches the body of knowledge in the sociology of religion, while practically it provides a basis for religious institutions to design more contextual guidance programs and opens avenues for further research on the impact of modernization and digital media on the transformation of religious practice.